The Next Generation of Anticancer Metallopharmaceuticals: Cancer Stem Cell‐Active Inorganics. (12th October 2018) - Laws, Kristine; Suntharalingam, Kogularamanan
Abstract: Cancer stem cells (CSCs) are heavily linked to fatal incidences of cancer relapse and metastasis. Conventional cancer therapies such as surgery, chemotherapy and radiation are largely futile against CSCs. Therefore, highly original approaches are needed to overcome CSCs and to provide durable, long‐term clinical outcomes. Many academia‐ and pharmaceutical‐led studies aimed at developing chemical or biological anti‐CSC agents are ongoing; however, the application of inorganic compounds is rare. In this minireview, we discuss how the chemical diversity and versatility offered by metals has been harnessed to develop an unprecedented, emerging class of metallopharmaceuticals: CSC‐active inorganics. A detailed account of their mechanism(s) of action is provided, and possible future directions for exploration are also put forward. Abstract : Metal complexes are used to treat several ailments, such as cancer, rheumatoid arthritis, peptic ulcers and bacterial and fungal infections. The use of inorganic compounds to treat cancer stem cells (CSCs), a clinically relevant sub‐population of tumours responsible for relapse and metastasis, is documented in this minireview, with a spotlight on their mechanism of action.